false
Small Michael Cho

Budget: $15

Solved!

If functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are givenIf functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are givenIf functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are givenIf functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are givenIf functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are givenIf functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are givenIf functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are givenIf functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are givenIf functions f(x) and g(x) are continuous everywhere and f(1) = 2, f(3) = -4, f(4) = 8, g(0) = 4, g(3) = -6 and g(7) = 0 then lim (f + g)(x) as x approaches 3 is equal to a. -10 b. -11 c. cannot find a value for the above limit since only values of the functions are given

Answer

Small Tutor Jack Kim

The answer is a. lim (f + g)(x) = lim f(x) + lim g(x) and since the two functions...